A Statistical Analysis of STEVE. Issue 11 (28th November 2018) - Gallardo‐Lacourt, Bea; Nishimura, Y.; Donovan, E.; Gillies, D. M.; Perry, G. W.; Archer, W. E.; Nava, O. A.; Spanswick, E. L.
Abstract: There has been an exciting recent development in auroral research associated with the discovery of a new subauroral phenomenon called STEVE (Strong Thermal Emission Velocity Enhancement). Although STEVE has been documented by amateur night sky watchers for decades, it is as yet an unidentified upper atmosphere phenomenon. Observed first by amateur auroral photographers, STEVE appears as a narrow luminous structure across the night sky over thousands of kilometers in the east‐west direction. In this paper, we present the first statistical analysis of the properties of 28 STEVE events identified using Time History of Events and Macroscale Interactions during Substorms (THEMIS) all‐sky imager and the Redline Emission Geospace Observatory (REGO) database. We find that STEVE occurs about 1 hr after substorm onset at the end of a prolonged expansion phase. On average, the AL index magnitude is larger and the expansion phase has a longer duration for STEVE events compared to subauroral ion drifts or substorms. The average duration for STEVE is about 1 hr, and its latitudinal width is ~20 km, which corresponds to ~¼ of the width of narrow auroral structures like streamers. STEVE typically has an equatorward displacement from its initial location of about 50 km and a longitudinal extent of 2, 145 km. Plain Language Summary: Strong Thermal Emission Velocity Enhancement (STEVE) is an atmospheric phenomenon that manifests across the night sky as an extremely thin yet long ribbon of vibrant purple and white hues. Although STEVE has been well documented by amateur auroral photographers for several decades, the scientific community only recently stumbled upon this phenomenon. In this paper, we report on the first statistical analysis of STEVE's optical characteristics using ground‐based all‐sky imagery and examined satellite data to determine the geomagnetic conditions favorable for the formation of STEVE. Our results verify that STEVE is narrow in the north‐south direction, but it extends over a wider east‐west region. We have also determined that STEVE displaces southward over its lifetime in most observations. More interestingly, all 28 STEVE events identified in this study were observed at the end of a prolonged substorm expansion phase. Key Points: The first statistical study of the subauroral optical phenomenon known as STEVE, featuring 28 events identified with all‐sky imagers, is performed STEVE is a latitudinally narrow optical structure: ~20 km in meridional spread and spanning over 2, 000 km zonally STEVE is strongly linked to substorms: It is observed subsequently to a prolonged (~1 hr) substorm expansion phase